PENGUJIAN SUDUT KONTAK PADA BAHAN ISOLASI RESIN EPOKSI DENGAN PENGISI PASIR PANTAI YANG MENGANDUNG BANYAK KALSIUM - M. Toni Prasetyo; Hamzah Berahim; T Haryono (PSTE UNIMUS, 2012)
Formation tracking power (electrical tracking) on the surface of an insulating material due to flashover continuously, especially when there are contaminants flotving on the surface of the insulating material. Due to electrical tracking the insulation material surface to be broken and easier flow of electric current. Insulating material must have good electrical characteristics leakage current is very small, the critical flashover voltage is very large and the surface is hydrophobic materials The material used in this study is an epoxy, resin insulating silicone rubber polymer with a fillerKukup beach sand containing a lot of caicium carbonate with stoichiomelric values (the ratio of materials and hardener or curing agent) is equal to 1, with values increasing sizefiller (filler) , 120x50 mm sample size. The study was conducted in the laboratory according to standard IEC 587: 1984. In this study, the effect of the variation of the filling of the contact angle and its influence on surface degradation caused by charging, were analyzed. The result showed that the epoxy resin used in this study whice are categorized partly wet (partially wetted) and approached hydrophobic. The more concentration of silicone rubber and sand as filler (filler.) will increase the hydrophobic nature of the contact angle shown is growing. lf the surface is hydrophobic, then the time required for the first discharge and breakdown on the surface of the old material.Keywords: epoxy resins, fillers, contact angle, hydrophobicity